Long-term oncological outcomes of laparoscopic versus transanal total mesorectal excision for mid-low rectal cancer: a propensity score matching analysis - Xie, Yang; Wang, Ziwei; Zhang, Hongyu (Frontiers in Oncology, 2026)
BackgroundTransanal total mesorectal excision (taTME) has become a promising surgical approach for anus-preserving surgery of mid-low rectal cancer (RC). This study aimed to compare the long-term oncological outcomes of taTME and laparoscopic total mesorectal excision (lapTME).MethodsOf 233 patients who were treated for mid-low RC from July 2017 to August 2020, 110 underwent taTME and 123 received lapTME. Propensity score matching (PSM) was performed to balance the baseline characteristics between the taTME and lapTME groups. After PSM, 61 patients were included in each group.ResultsPrior to PSM, the 5-year overall survival (OS) and disease-free survival (DFS) rates were comparable between the taTME and lapTME groups (72.7% vs. 69.1%, p = 0.617; 72% vs. 69%, p = 0.576, respectively). After PSM, there was no statistically significant difference in the 5-year OS and DFS rates between groups (64.2% vs. 64.4%, p = 0.936; 66.1% vs. 66.1%, p = 0.947, respectively).ConclusionAs compared to lapTME, taTME achieved comparable oncological safety for patients with mid-low RC.